Static Continuous Passive Motion (CPM) Machine Simulation Tackle Therapy with SolidWorks - Felix Krisna Aji Nugraha; Antonius Hendro Noviyanto; Baskoro Latu Anurogo (Politeknik Negeri Lhokseumawe, 2023)
Patients with joint injuries or after joint surgery are expected to perform the passive and continuous movement to avoid joint stiffness. This passive and continuous movement can be done with the help of a continuous passive motion machine (CPM machine). CPM machine is a therapeutic tool used to rehabilitate patients with joint injuries or post-joint surgery. In this study, a simulation test of therapeutic equipment for the ankle joint that can be moved rotationally will be carried out. The method that will be used in this research is the Finite Element Analysis (FEA) method to analyze and simulate the strength of the elements used in the design model. The results to be sought in this study are the results of the stress and yield strength of the tool, so that the safety of the tool design will be known. The simulation results using carbon iron get a maximum stress of 3.012x105 N/m2 and yield strength of 2.20594x108. Based on the results obtained in this study, it can be concluded that the CPM machine design is safe and strong to be realized